Cataract surgery for falls prevention and improving vision: modelling the health gain, health system costs and cost-effectiveness in a high-income country. Issue 4 (20th June 2019) - Boyd, Matt; Kvizhinadze, Giorgi; Kho, Adeline; Wilson, Graham; Wilson, Nick
Abstract : Aim: To estimate the health gain, health system costs and cost-effectiveness of cataract surgery when expedited as a falls prevention strategy (reducing the waiting time for surgery by 12 months) and as a routine procedure. Methods: An established injurious falls model designed for the New Zealand (NZ) population (aged 65+ years) was adapted. Key parameters relating to cataracts were sourced from the literature and the NZ Ministry of Health. A health system perspective with discounting at 3% was used. Results: Expedited cataract surgery for 1 year of incident cases was found to generate a total 240 quality-adjusted life years (QALYs) (95% uncertainty interval (UI) 161 to 360) at net health system costs of NZ2.43 million (95% UI 2.02 to 2.82 million) over the remaining lifetimes of the surgery group. This intervention was cost-effective by widely accepted standards with an incremental cost-effectiveness ratio (ICER) of NZ10 600 (US7540) (95% UI NZ6030 to NZ15 700) per QALY gained. The level of cost-effectiveness did not vary greatly by sex, ethnicity and previous fall history, but was higher for the 65–69 age group compared with the oldest age group of 85–89 years (NZ7000 vs NZ14 200 per QALY gained). Comparing cataract surgery with no surgery, the ICER was even more favourable at NZ4380 (95% UI 2410 to 7210) per QALY. Considering only the benefits for vision improvement and excluding the benefits of falls prevention, it was still favourable at NZ9870 per QALY. Conclusions: Expedited cataract surgery appears very cost-effective. Routine cataract surgery is itself very cost-effective, and its value appears largely driven by the falls prevention benefits.